Stromal Compartment as a Survival Prognostic Factor in Advanced Ovarian Carcinoma. Issue 1 (1st January 2010) - Labiche, Alexandre; Heutte, Natacha; Herlin, Paulette; Chasle, Jacques; Gauduchon, Pascal; Elie, Nicolas
Abstract : Objective: We investigated the prognostic significance of stromal compartment on the overall survival of patients with advanced epithelial ovarian cancer. Methods: We evaluated retrospectively the stroma proportion of the tumor surgical specimens of 194 patients with stages III and IV disease, using histochemical staining and fully automatic virtual slide processing. The prognostic significance of stroma proportion and clinical parameters were evaluated using log-rank test and Cox regression. Results: Stroma proportion was found to be an independent prognostic factor by both univariate ( P = 0.016) and multivariate analyses (hazards ratio = 1.45, P = 0.011). Conclusion: The present data indicate that a high stroma proportion is related to a poor prognosis of stage III and IV ovarian carcinomas.